(3GdQMeI aj GdWH hGdMceIs - (3eMeO GdegOj Hf EHQGgje GdUHjQj Gdjefj GdgfOj,J (B815 (3g` s
(3ChdgG (B:s
(3aj HdOfG EPG cGf ZjQ eUeJ EPG CQOJ eYQaI Pdc s
(3BNQgG (B:s
(3eHJhQI GdBNQ , hBNQ efgG HaUd aj GdCeRLI(B: (3CYde Cf GdeRGL GdWHjYi jbY aj GdCHOGf aGfbSe Edi NeSI CeRLI, GdeRGL GdChd GdUHQGhi s
(3bWYI ef fSNI SGOSIs
(3eY edGMXI YOe GYJeGO GdJQbje GdehLhOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B100 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdWHs